2006
DOI: 10.1097/01.ta.0000240460.35245.1a
|View full text |Cite
|
Sign up to set email alerts
|

Mental Illness as an Independent Risk Factor for Unintentional Injury and Injury Recidivism

Abstract: Mental illness is an independent risk factor for unintentional injury and injury recidivism. Individuals with mental illness also have a different pattern of injury and hospitalization. They tended to suffer from different mechanisms of injury, stayed in the hospital longer, and were more likely to be discharged to a skilled nursing facility. Recognition of mental illness as a risk factor for injury may prompt re-examination of resource allocation for mental health and injury prevention and highlights the ment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

15
93
0
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 141 publications
(111 citation statements)
references
References 18 publications
15
93
0
3
Order By: Relevance
“…Consistent with findings from previous studies [1][2][3][4][5][6][7][8][9][10], it was observed that participants with mental health conditions and who required mental health services were at an increased risk of injury. It was also observed that continuous mental health treatment pattern without interruption or window periods was associated with lower risk of injury compared to those with treatment interruption or window periods.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…Consistent with findings from previous studies [1][2][3][4][5][6][7][8][9][10], it was observed that participants with mental health conditions and who required mental health services were at an increased risk of injury. It was also observed that continuous mental health treatment pattern without interruption or window periods was associated with lower risk of injury compared to those with treatment interruption or window periods.…”
Section: Discussionsupporting
confidence: 81%
“…Findings are largely consistent, suggesting that patients with mental conditions are at an increased risk of both intentional and unintentional injuries [1][2][3][4][5][6][7][8][9][10]. Mental illness has been shown to be highly prevalent in various cultures and mental health services are often unable to meet treatment needs [11][12][13][14][15][16].…”
Section: Introductionsupporting
confidence: 51%
See 1 more Smart Citation
“…[1][2][3][4] Although several studies have examined health outcomes associated with homelessness using European samples, national studies among U.S. homeless are scant. 5,6 The majority of available research has been largely focused on geographically limited cohorts in major U.S. cities, [7][8][9][10][11][12][13][14][15] failing to provide a comprehensive examination of salient public health problems within homeless populations. Given the differences in health care systems and social care systems in the United States and European countries, it is useful to specifically examine U.S. homeless populations to better understand public health issues affecting this population.…”
mentioning
confidence: 99%
“…Moreover, physical impairment can influence psychological health (Garralda, 1994;Rangel, Garralda, Hall & Woodham, 2003) while psychological aspects, such as stress, can influence the physical reaction of the body (Ljung & Friberg, 1994). Furthermore psychological problems tend to increase the risk of accidental injuries (Wan, Morabito, Khaw, Knudson & Dicker, 2006). However, while considering all of the above, health development and the consequences of health conditions will invariably be influenced by each unique child's individual conditions (Heinonen, Metteri, & Leach, 2009;Sarafino, 2006) as well as their social and cultural environment (Gironda et al, 2006;Park et al, 2009;Power & Kuh, 2006;Robertson, Brunner, & Sheiham, 2006;Shaw, Dorling & Smith, 2006).…”
Section: Introductionmentioning
confidence: 99%